2012
DOI: 10.1093/humrep/des417
|View full text |Cite
|
Sign up to set email alerts
|

Use of hyaluronan in the selection of sperm for intracytoplasmic sperm injection (ICSI): significant improvement in clinical outcomes—multicenter, double-blinded and randomized controlled trial

Abstract: STUDY QUESTIONDoes the selection of sperm for ICSI based on their ability to bind to hyaluronan improve the clinical pregnancy rates (CPR) (primary end-point), implantation (IR) and pregnancy loss rates (PLR)?SUMMARY ANSWERIn couples where ≤65% of sperm bound hyaluronan, the selection of hyaluronan-bound (HB) sperm for ICSI led to a statistically significant reduction in PLR.WHAT IS KNOWN AND WHAT THIS PAPER ADDSHB sperm demonstrate enhanced developmental parameters which have been associated with successful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 33 publications
11
114
1
7
Order By: Relevance
“…A similar increase in IR, CPR, and lower PLR values was found by Worrilow and colleagues [Worrilow et al 2006;Worrilow et al 2007;Worrilow et al 2012]. Others compared conventional sperm selection and the use of sperm selected from a liquid source of HA and an increased IR was found [Parmegiani et al 2010].…”
Section: Discussionsupporting
confidence: 67%
“…A similar increase in IR, CPR, and lower PLR values was found by Worrilow and colleagues [Worrilow et al 2006;Worrilow et al 2007;Worrilow et al 2012]. Others compared conventional sperm selection and the use of sperm selected from a liquid source of HA and an increased IR was found [Parmegiani et al 2010].…”
Section: Discussionsupporting
confidence: 67%
“…Recently in 2013, in a large multi-centric trial, Worrilow et al [15], reported a greater implantation rate and clinical pregnancy rate along with a statistically significant lower pregnancy loss rate when hyaluronan bound sperm was used for ICSI. However, this improvement was only attributed to patients demonstrating a compromised hyaluronan binding assay (HBA) score.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently a large study comparing ICSI using HA and conventional ICSI showed no statistical difference in embryo quality and pregnancy rates [12]. Moreover, improvement in fertilization rate and pregnancy rates has been observed only in semen samples exhibiting either poor morphology [13] or compromised HA binding [14,15]. This suggests that while PICSI might prove to be a valuable tool for sperm selection in patients with male factor infertility, its role needs to be further investigated in patient populations other than male factor infertility.…”
Section: Introductionmentioning
confidence: 99%
“…sHABA has proved useful in selecting spermatozoa with a high DNA integrity and morphology and may sometimes be used as a screening test for sperm quality before IVF (Worrilow et al 2013). However, its use remains controversial as sHABA does not predict freeze-thawing sperm survival (Boynukalin et al 2012), and it does not predict the pregnancy rates either in intrauterine insemination (Yogev et al 2010) or IVF (Ye et al 2006, Boynukalin et al 2012.…”
Section: Sperm-related Functionsmentioning
confidence: 99%